ØªØÙ„ÙŠÙ„ Ø§Ù„Ø¬Ù…Ù„Ø© Ø§Ù„Ø§Ø³Ù…ÙŠØ© ÙÙŠ ÙƒØªØ§Ø¨ Ø§Ù„Ø£Ø®Ù„Ø§Ù‚ Ù„Ù„Ø¨Ù†ÙŠÙ† Ø§Ù„Ø¬Ø²Ø¡ Ø§Ù„Ø£ÙˆÙ„ Ø§Ù„Ø°ÙŠ Ø£Ù„ÙÙ‡ Ø¹Ù…Ø± Ø¨Ù† Ø£ØÙ…Ø¯ Ø¨Ø§Ø±Ø¬Ø§Ø¡ - Handriawan, Doni; Hairi, Hamam (-)
One of the fundamental rules in composing Arabic sentences is the tarkib jumlah ismiyah structure. This research aims to analyze types and patterns of jumlah ismiyah structure used in kitab "al-Akhlaq li Al-Banin" first juz, which consists of 33 chapters. The book written by Umar bin Ahmad Baraja is a famous book studied in various classical Islamic boarding schools in Lombok. It makes this study quite interesting because, in addition to the requirements with the content of educational values for children, this analysis is also expected to add the vocabularies of Arabic studies. This research is library research using qualitative methods. Meanwhile, in data collection and analysis, documentation techniques and inductive descriptive analysis are used. The results of this study indicate that there are 66 compositions or tarkib jumla ismiyyah in this book, both from the aspect of its mubtada' and from the part of its khabar.